Clathrin mediated endocytosis in Alzheimer’s disease: cell type specific involvement in amyloid beta pathology - Jaye, Sierra; Sandau, Ursula S.; Saugstad, Julie A. (Frontiers in Aging Neuroscience, 2024)
This review provides a comprehensive examination of the role of clathrin-mediated endocytosis (CME) in Alzheimer’s disease (AD) pathogenesis, emphasizing its impact across various cellular contexts beyond neuronal dysfunction. In neurons, dysregulated CME contributes to synaptic dysfunction, amyloid beta (Aβ) processing, and Tau pathology, highlighting its involvement in early AD pathogenesis. Furthermore, CME alterations extend to non-neuronal cell types, including astrocytes and microglia, which play crucial roles in Aβ clearance and neuroinflammation. Dysregulated CME in these cells underscores its broader implications in AD pathophysiology. Despite significant progress, further research is needed to elucidate the precise mechanisms underlying CME dysregulation in AD and its therapeutic implications. Overall, understanding the complex interplay between CME and AD across diverse cell types holds promise for identifying novel therapeutic targets and interventions.